21.15%‐Efficiency and Stable γ ‐CsPbI3 Perovskite Solar Cells Enabled by an Acyloin Ligand. Issue 12 (10th February 2023) - Wang, Jungang; Che, Yuhang; Duan, Yuwei; Liu, Zhike; Yang, Shaomin; Xu, Dongfang; Fang, Zhimin; Lei, Xuruo; Li, Yong; Liu, Shengzhong (Frank)
Abstract: Cesium lead triiodide (CsPbI3 ) is a promising light‐absorbing material for constructing perovskite solar cells (PSCs) owing to its favorable bandgap and thermal tolerance. However, the high density of defects in the CsPbI3 film not only act as recombination centers, but also facilitate ion migration, leading to lower PCE and inferior stability compared with the state‐of‐the‐art organic–inorganic hybrid PSC counterpart. Theoretical analyses suggest that the effective suppression of defects in CsPbI3 film is helpful for improving the device performance. Herein, the stable and efficient γ ‐CsPbI3 PSCs are demonstrated by developing an acyloin ligand (1, 2‐di(thiophen‐2‐yl)ethane‐1, 2‐dione (DED)) as a phase stabilizer and defect passivator. The experiment and calculation results confirm that carbonyl and thienyl in DED can synergistically interact with CsPbI3 by forming a chelate to effectively passivate Pb‐related defects and further suppress ion migration. Consequently, DED‐treated CsPbI3 PSCs yield a champion PCE of 21.15%, which is one of the highest PCE among all the reported CsPbI3 PSCs to date. In addition, the unencapsulated DED‐CsPbI3 PSC can retain 94.9% of itsinitial PCE when stored under ambient conditions for 1000 h and 92.8% of its initial PCE under constant illumination for 250 h. Abstract : An acyloin ligand (1, 2‐di(thiophen‐2‐yl)ethane‐1, 2‐dione (DED)) is developed to construct γ‐CsPbI3 perovskite solar cells (PSCs). Comprehensive characterizations confirm that the carbonyl and thienyl in DED can synergistically bind with Pb 2+ ‐related defects by forming a chelate (one DED bind with two Pb 2+ ions), yielding a stable γ‐CsPbI3 film. Consequently, DED‐CsPbI3 yields a champion PCE of 21.15% among the reported CsPbI3 PSCs to date.